A Simulation-Based Approach To Spiral Pump Design - Hengky Luntungan; Stenly Tangkuman; Benny L. Maluegha (International Journal of Applied Sciences and Smart Technologies, 2026)
The consistent availability of irrigation water in agricultural areas remains a challenge to this day, due to the fact that rivers are always located at a lower elevation than farmland. As an alternative solution, a spiral pump has been introduced that operates solely using the kinetic energy of river water flow, unlike conventional water pumps that always require electricity or fossil fuels. This study aims to develop a simulation-based spiral pump design by integrating findings from previous analyses regarding fluid flow behavior and water wheel performance. Accordingly, using SolidWorks software, a comprehensive geometric model of the spiral pump was created, consisting of a 1.2-meter-diameter undershot water wheel, an eight-coil spiral hose with a 2-inch diameter, and a support frame. Through static structural simulation, it was also determined that a hydraulic force of 72.63 N and a torque of 32.68 Nm act on the water wheel, with the shaft withstanding a force of 174.06 N. The von Mises stress on the shaft is 3.746 × 10⁶ N/m², while on the blades it is 1.711 × 10⁷ N/m²; these stress values are well below the yield strength of A36 steel for the shaft and aluminum alloy for the blades. Thus, based on CFD-based flow rate analysis, hydraulic head evaluation, and structural validation, this study has produced an integrated design that ensures operational efficiency and structural safety. This spiral pump design can be developed into a prototype for field application as a cost-effective renewable energy solution.